Análisis de los métodos de control del Acaro Varroa destructor (Oudemans 1904) de colmenas sobre abejas Apis mellifera productoras de miel - Fernández Chaguay, Cristian Francisco (2022)
Beekeeping, in production contexts, has tried to combat varroa parasitosis through the use of different treatments; however, in recent years, despite its continuous changes, it has been shown that V. destructor has been fully resistant to certain acaricides, so it is important to identify the attitude of the parasite against different acaricides. The Integrated Management of the Apiary and the Good Beekeeping and Manufacturing Practices indicate the current trend of attention to an apiary. The disease responsible for the greatest loss of hives is varrhosis caused by the mite V. destructor, so this study is induced in order to seek and identify the greatest efficacy in relation to the different methods of control of the parasite worldwide and demonstrating the efficacy of different acaricides. This research raises the need to continue receiving feedback based on local and international studies. In this way, a compilation of information will be obtained that will allow the "eradication" of varrhosis to continue, which is responsible for the highest mortality rate of hives from the health point of view.